2018
DOI: 10.12659/msm.911672
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Simple Functional Tests to Predict Attrition from Combat Service in Female Light Infantry Soldiers

Abstract: BackgroundWorldwide, there is a high attrition rate, or dropout rate, from combat in trained soldiers, mainly due to musculoskeletal injuries. This study aimed to determine whether the use of an upper limb stability test, the Upper Quarter Y-Balance Test (UQYBT), and a modified version of the Ranger Test (MRT) that included a lower limb step-up endurance test, could predict attrition from combat service in female infantry soldiers.Material/MethodsIn 2015, a group of 167 newly recruited female light infantry so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…A limitation to study by Saxon et al (2020) is that only statistics of group comparisons were conducted without more sophisticated statistical methods such as regressions, and thus relationships with adjusted confounders were not reported. Another study by Gottlieb et al (2020) found that a modified loaded submaximal endurance test was associated with attrition for 18 months of infantry training in women, whereas upper limb stability test was not [11]. The present study findings together with the very few recent study results [3,11] may indicate that selected physical fitness components are related to dropout phenomenon, showing most promise in aerobic fitness.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…A limitation to study by Saxon et al (2020) is that only statistics of group comparisons were conducted without more sophisticated statistical methods such as regressions, and thus relationships with adjusted confounders were not reported. Another study by Gottlieb et al (2020) found that a modified loaded submaximal endurance test was associated with attrition for 18 months of infantry training in women, whereas upper limb stability test was not [11]. The present study findings together with the very few recent study results [3,11] may indicate that selected physical fitness components are related to dropout phenomenon, showing most promise in aerobic fitness.…”
Section: Discussionsupporting
confidence: 51%
“…Another study by Gottlieb et al (2020) found that a modified loaded submaximal endurance test was associated with attrition for 18 months of infantry training in women, whereas upper limb stability test was not [11]. The present study findings together with the very few recent study results [3,11] may indicate that selected physical fitness components are related to dropout phenomenon, showing most promise in aerobic fitness. However, future studies are warranted to gain more insight in this particular research issue in military settings.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations